PENGGUNAAN SAW UNTUK ANALISIS PROSES PEREBUSAN KEDELAI DALAM PRODUKSI TEMPE - Dana Marsetiya Utama; Teguh Baroto (AGROINTEK, 2018)
This article describes assessment organoleptic quality in boiling process soybean at production tempe. we proposed the model for selecting boiling process soybean based on quality organoleptic. We used pairwise comparison and SAW the problem. Pairwise comparison used to determine to weigh for organoleptic criteria. SAW used for selecting boiling process alternative. the result of proposed pairwise comparison and SAW model showed this model effective for assessment organoleptic quality in boiling process soybean at production tempe.